Estudos do reaproveitamento térmico do bagaço de laranja: secagem em leito de jorro modificado e peletização - Pinto, Guilherme Henrique Alves (Universidade Federal de São Carlos, 2024)
The use of biomass as an alternative source of renewable energy has been gaining ground and leading to innovations in the production sector, seeking to support sustainable development and dispose of waste that was previously discarded. Brazil stands out as one of the world's leading producers of oranges, being the largest exporter of juice. Orange pomace, an abundant by-product with largely untapped potential as a biofuel, requires technical improvements to render its use viable. The present work aimed to evaluate the drying of orange pomace in a spouted bed to obtain dry biomass for pelletization. This evaluation involved studying the influence of a CaO mixture combined with pressing as pre-treatment, assessing the fluid dynamics in both the conventional spouted bed (LJC) and the spouted bed with mechanical agitation (LJMM) equipped with inclined blades, with variations in the bed's static height. Drying experiments were conducted in the LJMM, altering air temperature from 40 to 80 °C and air flow from 1 to 5 times the minimum spout velocity. These variations were analyzed for their impact on drying time and the quality of the resulting pellets. The obtained dry biomass underwent pelletization using three distinct strategies to enhance its physical and mechanical properties: particle size reduction, inclusion of binders, and torrefaction. The pellets were subjected to characterization tests measuring durability, impact resistance, density, water absorption, as well as aging properties such as changes in color, density, and humidity over time. The addition of quicklime with pressing removed 31.7% of the initial moisture from the bagasse, facilitating some movement in the LJC. However, the process faced instability due to biomass cohesion. Mechanical agitation proved essential in enhancing operational stability by agitating the entire bed, increasing stability, and eliminating fines carryover, up to 11.65% for LJC, allowing for a bed height of 27 cm, higher than the maximum 21.1 cm for LJC. Fluid dynamics analysis for the LJMM indicated an increase in pressure drop with rising bed height, while this correlation was absent for the minimum operating speed. This suggested that agitation primarily facilitated particle motion and air movement expanded the bed. The LJMM's operating air velocity was measured at 1.10±0.14 m/s, significantly lower (90%) compared to the minimum spout velocity required for a 21.12 cm height (11.11 m/s). During biomass drying, saturation of moisture in the gas stream at the LJMM exit highlighted efficient energy utilization, signifying an adequate airflow supplied to the system. Temperature and drying air flow showed no significant influence on pellet properties. Pellets produced from dried bagasse failed to attain desired physical and mechanical properties, necessitating particle size reduction to eliminate predetermined fragility points due to coarse particles. Strategies involving the addition of solid carbohydrates and mixing with coffee grounds altered pellet mechanical properties but fell short of achieving desirable values. Torrefaction imparted some hydrophobicity to the biomass, ensuring adequate water absorption, albeit resulting in fragile pellets. The addition of molasses enhanced pellet density and strength, but pellets expanded during a 30-day storage period. However, the addition of pure water or gelatinized starch produced resilient pellets, exhibiting high durability and impact resistance, maintaining structural integrity even after storage. These pellets also met the density threshold of 1200 kg/m³ with minimal color variation. These outcomes underscored the significance of moisture as a binding agent, allowing for the integration of drying and pelletization, ensuring an economically and operationally viable process.
Studies on the thermal reuse of orange pomace: drying in a modified spouted bed and pelletization
Keywords: Agitação mecânica; Reaproveitamento de biomassas; Combustão; Secagem; Mechanical agitation; Biomass reuse; Combustion; Drying; ENGENHARIAS::ENGENHARIA QUIMICA